Digitalisasi Akses Pemohon di Mahkamah Konstitusi: Antara Efisiensi Prosedural dan Fragmentasi Due Process of Law - Daniel Tata Gabe; Meiddy Dwi Darmawan; Nur Ramadhan Alqadr; Sidi Ahyar Wiraguna (Jurnal Hukum Lex Generalis, 2026)
The digitalization of petitioner access in judicial review at the Constitutional Court (MK) creates a paradoxical impact: procedural efficiency increases, yet due process guarantees become fragmented. This normative juridical research analyzes MK internal regulations (PMK No. 2/2021) and the implementation of e-filing and hybrid hearing systems. The main findings reveal that the absence of standardized electronic document authentication, algorithmic legal standing verification without clarification mechanisms and inadequate petitioner data protection constitute primary sources of procedural fragmentation. This study recommends reforming PMK to accommodate cybersecurity standards and alternative access mechanisms for petitioners with digital limitations.